Proceedings of the 3rd Workshop on Predicting and Improving Text Readability for Target Reader Populations (PITR) 2014
DOI: 10.3115/v1/w14-1209
|View full text |Cite
|
Sign up to set email alerts
|

Improving Readability of Swedish Electronic Health Records through Lexical Simplification: First Results

Abstract: This paper describes part of an ongoing effort to improve the readability of Swedish electronic health records (EHRs). An EHR contains systematic documentation of a single patient's medical history across time, entered by healthcare professionals with the purpose of enabling safe and informed care. Linguistically, medical records exemplify a highly specialised domain, which can be superficially characterised as having telegraphic sentences involving displaced or missing words, abundant abbreviations, spelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Such characterization is essential for constructing automated language analysis tools that can be used for knowledge extraction from clinical text. It has previously been found that many words and expressions in Swedish clinical free text cannot be automatically identified by vocabulary matching to established terminologies (Skeppstedt et al 2012, Grigonytė et al 2014). This is in part due to medical jargon and the extensive use of ad hoc abbreviations (Kvist & Velupillai 2014), but also misspellings and foreign words.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such characterization is essential for constructing automated language analysis tools that can be used for knowledge extraction from clinical text. It has previously been found that many words and expressions in Swedish clinical free text cannot be automatically identified by vocabulary matching to established terminologies (Skeppstedt et al 2012, Grigonytė et al 2014). This is in part due to medical jargon and the extensive use of ad hoc abbreviations (Kvist & Velupillai 2014), but also misspellings and foreign words.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compare two cases: senso ri + n euralt and fiber + rin oskopi . The compound splitting that we employ in this study is based on using a large general language Swedish dictionary (The NST Dictionary 2007) and a medical domain dictionary, resulting in a precision of 83.5%, and is described in more detail in Grigonytė et al (2014).…”
Section: Methodology For Detecting Affix Use In Clinical Textsmentioning
confidence: 99%
See 1 more Smart Citation
“…We developed FreeLing-Med, a toolkit to analyze documents in the biomedical domain in Spanish and English [26,27]. The resulting domain-adapted FreeLingMed system is able to carry out medical named entity recognition, linking of all the terms in SNOMED CT with their corresponding semantic tag (substances, disorders, procedures, findings), and identification of all the medical abbreviations using the dictionary by Yetano and Alberola [28] as well as the identification of brand-drug names using a drug database called BOTPLUS 5 . In addition, the original FreeLing adds semantic and syntactic pieces of information.…”
Section: Freeling-medmentioning
confidence: 99%
“…Furthermore, most NLP work in biomedicine has concerned English (although there are recent efforts that incorporate other languages, such as Spanish [2], French [3,4], Swedish [5], and Finnish [6]). …”
Section: Introductionmentioning
confidence: 99%